Analisis Tingkat Kepuasan Konsumen terhadap Atribut Produk Sambal Stroberi di Haifresh Strawberry Lembang - Deta Najma Ambarwati; Veralianta Br Sebayang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Developments in the food industry are driving businesses to produce innovative products that align with consumer preferences. One such product innovation developed by Haifresh Strawberry Lembang is strawberry sambal as a processed product. Fluctuations in sales indicate the need to evaluate product attributes to determine the level of consumer satisfaction, which will serve as the basis for improving these attributes and formulating product development strategies. This study aims to identify consumer characteristics and the level of consumer satisfaction with the attributes of strawberry sambal based on the 4P dimensions. The methods used include the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA). The results show that strawberry sambal consumers are predominantly women aged 26–35, the majority of whom reside in the Bandung area. Most are homemakers or private-sector employees. Consumer satisfaction with the strawberry sambal product falls into the “satisfied” category, with a CSI score of 75.03%, indicating that most product attributes meet consumer expectations. The IPA analysis shows that there are three attributes in Quadrant I—namely, packaging design, ease of access to the product, and online promotions and information—that are top priorities for improvement because they have a high level of importance but the company’s performance in these areas is low. The results of this study are expected to serve as the basis for determining improvements and enhancement strategies for these product attributes, thereby increasing consumer satisfaction.